Missouri's Twin Traumas, 1, The Stephan Crisis (1839-) - Diefenthaler, Jon (Lutheran quarterly, 2025)
In view of two recent anniversaries, the 175th of its founding in 1847 and the fiftieth of the "Walk Out" of faculty and students in 1974 at its St. Louis seminary, the Lutheran Church—Missouri Synod (LCMS) through its Concordia Historical Institute has published several volumes that highlight two traumatic moments in its history. One of them is a new translation of The Emigration of the Saxon Lutherans in the Year 1838 and Their Settlement in Perry County, Missouri, written in German by an LCMS pastor, Johannes Friedrich Koestering, twenty-five years after its immigrant forebears arrived in America. The book provides an account of the exposure and exile of Martin Stephan, a bishop to whom these Saxons had given total authority in ecclesiastical and civil matters. The traumatic effects of this crisis were not only immediately felt but help explain the subsequent behavior of "Missouri" as a church body. Chief among them are its unequivocal allegiance to its own brand of Lutheran orthodoxy, its insistence upon complete agreement in matters of doctrine and church practice for ecclesiastical fellowship of any kind, and its tendency to isolate itself protectively from key features of America's culture. As a subsequent article will demonstrate, the second traumatic moment created by the "Walk Out," named more often as "Seminex" and featured in other recent LCMS anniversary publications, only reinforced these same effects of the Stephan crisis. These incidents shed light on where "Missouri" has positioned itself in the world of the twenty-first century.